The mask of sanity: an attempt to clarify some issues about the so-called psychopathic personality - Cleckley, Hervey M. (Mosby, 1976)
"Since the last edition of this book was prepared, many additional psychopaths have been observed pursuing their vivid patterns of maladjustment. A few encouraging reports of successful therapeutic measures have emerged. The number of patients concerned is, however, too small to furnish substantial evidence that a regularly effective means of dealing with the psychopath's disorder has been discovered. It is my increasingly strong belief that the immediate and practical goal of all concerned with this problem should be to promote a general understanding that these people have a social disability that is real and extremely serious. Adequate means must be provided to control legally these severely disordered patients like those long ago provided, and available today, for far less incompetent patients of other types. Even if a truly curative therapy is never devised, perhaps half the damage, crime, waste, useless disorder, and sorrow caused now by psychopaths could be eliminated by a reasonably wise use of such legal measures for control. In the present revision I have attempted to make clearer my concepts of the psychopath's confusing and paradoxical disorder. It is not easy to convey this concept, that of a biologic organism outwardly intact, showing excellent peripheral function, but centrally deficient or disabled in such a way that abilities, excellent at the only levels where we can formally test them, cannot be utilized consistently for sane purposes or prevented from regularly working toward self-destructive and other seriously pathologic results. Impressed by its effectiveness as used by Henry Head to distinguish a complex and deep type of aphasia, I chose the term semantic to indicate my concept of a personality disorder which appears to have, at least hypothetically, some important similarities"--Preface. (PsycINFO Database Record (c) 2007 APA, all rights reserved)